2019
DOI: 10.1080/01639625.2019.1635861
|View full text |Cite
|
Sign up to set email alerts
|

White Collar Criminals’ Experience of Imprisonment in England and Wales: Revisiting the ‘special Sensitivity’ Debate

Abstract: This article explores white collar criminals' experience of imprisonment in England and Wales.Based upon interviews with 13 convicted offenders after they had completed their imprisonment, it is the first study to date of this kind in England and Wales (all others have been based in prison). It offers a unique impartial insight of prisoners' experience, beyond the influence of the prison walls. The paper explores the experience around the largely American 'special sensitivity' debate, over whether such offende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Even without the involvement of other inmates and prison guards, detention was accompanied by various impositions. As in prior research (Benson & Cullen 1988, Button et al 2020, the white-collar offenders studied linked their emotional distress primarily to the first fortnight of confinement, directly after they were jolted out of their professional and familial life and thrust into radically altered social settings. Three participants confessed suicidal ideation during that period, and a further three reported some symptoms of mental breakdown.…”
Section: Prison Timementioning
confidence: 98%
See 4 more Smart Citations
“…Even without the involvement of other inmates and prison guards, detention was accompanied by various impositions. As in prior research (Benson & Cullen 1988, Button et al 2020, the white-collar offenders studied linked their emotional distress primarily to the first fortnight of confinement, directly after they were jolted out of their professional and familial life and thrust into radically altered social settings. Three participants confessed suicidal ideation during that period, and a further three reported some symptoms of mental breakdown.…”
Section: Prison Timementioning
confidence: 98%
“…Qualitative research to date has delivered valuable insights into the lives of those few whitecollar offenders who have served time for their crimes. In their recent paper, Button et al (2020) have listed 14 previous studies based on interviews with convicted white-collar offenders, of which, however, only four addressed prison experience. Benson's pioneering article (1988) has shown that white-collar offenders being studied distanced themselves from prison subculture, stuck to their middle-class identities and actively neutralised the criminal label through a obsequious observance of rules and associating with other former professionals.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations